Traditional Uses, Pharmacological Efficacy, and Phytochemistry of Moringa peregrina (Forssk.) Fiori. —A Review - Senthilkumar, Annadurai; Karuvantevida, Noushad; Rastrelli, Luca; Kurup, Shyam S.; Cheruth, Abdul J. (Frontiers in Pharmacology, 2018)
Moringa is a sole genus of Moringaceae family with 13 species distributed in the tropical and sub-tropical regions. Among them, Moringa peregrina is one of the species which has wide range of traditional, nutritional, industrial and medicinal values. The plant parts are used in folk medicine for many human health care purposes including diabetes, wound healing, disinfectant, fever, constipation, muscle pains, slimness, burns, labour pain, hypertension, malaria, stomach disorder, asthma, skin problems and to expel a retained placenta. In addition to medicinal value, M. peregrina has cultural, spiritual and religious connections with the native people of Arabian Peninsula. M. peregrina plant parts were tested for many pharmacological activities viz, antioxidant, anti-microbial, anti-diabetic, anti-spasmodic, hypertension, hepatotoxicity, lipid lowering activity, anti-inflammatory, anti-cancer and memory disorders. Few active molecules belong to the class isothiocyanate, flavonoid, triterpenoid, phytosterol, polyphenol and glycoside were also isolated, identified and reported for anti-microbial, anti-oxidant, anthelmintic, anti-mutagenic, neuroprotective, anti-cancer, anti-hypertensive, anti-diabetic, anti-infective, anti-allergic, anti-inflammatory, herbicidal, lipid lowering potential, anti-trypanosomal and cytotoxic activities. So, the aim of the present review is to provide comprehensive information from recognized sources on the traditional uses, pharmacological efficacy and phytochemistry of the desert medicinal plant, M. perigrina. The information provided in this review will be very useful for further studies to develop novel therapeutic drugs.